The effect on synaptic physiology of synaptotagmin mutations in Drosophila. - DiAntonio, A.; Schwarz, T.L. (Neuron, 1994)
Synaptotagmin is a synaptic vesicle protein implicated in neurotransmitter release. Molecular characterization of four mutant alleles of this protein in Drosophila melanogaster has permitted an investigation of synaptotagmin's role in synaptic physiology and of some of the structural requirements for its function. Reduced levels of synaptotagmin resulted in a substantial alteration in synaptic function in the eye and at larval neuromuscular junctions. Decreased neurotransmitter release caused smaller evoked synaptic potentials. However, the frequency, but not the size, of spontaneous quantal events was simultaneously increased. These abnormalities do not appear to be secondary to a detectable morphological change in the arborization of the synapse. The increased frequency of spontaneous events was insufficient to deplete significantly the vesicle supply and thereby account for reduced transmission. These data are discussed in the context of models in which synaptotagmin's function includes a role in vesicle docking.